Implementasi Kinerja Mesin Pemotong Kemplang Khas Palembang Berbasis Teknologi Internet Of Things (IOT) - slamet WIDODO; A.Bahri Joni M; Ahyar Supani (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Palembang is one of the areas in Indonesia that is known to have culinary tastes that are distinctive and delicious. The capital city of South Sumatra Province has a very diverse culinary wealth. Kemplang Palembang Fish Crackers is one of the traditional Palembang food with fish and tapioca flour as its ingredients. At this time many fish kemplang makers still use traditional methods using brass pirikan, with a large variety of holes at the bottom. This phenomenon is also carried out by DPTM program partners, namely Partners (1) Kemplang cracker business "Lebak keranji; Partners (2) Kemplang Crackers Business "Matahari 222" on the Lunjuk Jaya Bukit Besar street in Palembang. Some of the obstacles faced by the kemplang cracker business to 2 (two) partners were a problem when the process of making pieces of several types of crackers was still using traditional and still very simple printing tools made from hand knives. The absence of an automatic cutting machine that can calculate the amount of production and can be monitored online for cutting logs of kemplang fish crackers so that it requires a large number of craftsmen and takes a long time. To overcome this problem it is deemed necessary for machines to print and cut kemplang crackers using automatic machines using an Internet of Things based microcontroller.